Penerapan Metode Web Engineering dalam Pembangunan Sistem Pengelolaan Gedung Olahraga Badminton Berbasis Web - Latifah, Ayu; Baswardono, Wiyoga; Ahdan, Alfin Muhamad; Aisyah, Risa (Jurnal Algoritma, 2023)
Currently, the benefits of using information technology have an impact on the human environment, one of which is the management of badminton sports halls. Badminton sports hall management is needed by badminton sports hall managers to make it easier to manage finances and make it easier to order badminton sports halls. Badminton sports hall management is still done manually, such as financial management which requires detailing income and expenditure data, resulting in less efficiency in badminton sports hall management. Apart from that, the public does not know about the existence of badminton sports halls due to lack of information. In the schedule ordering process, sports hall users must come directly to the venue, but sports hall users may not necessarily get the desired schedule availability, resulting in less time effectiveness and cost savings. This research aims to build a web management system for badminton sports halls to make it easier for badminton sports users in the scheduling process and make it easier for sports hall owners to manage their finances. The Web Engineering method was used in developing this application with the stages of communication, planning, modeling, construction and deployment, with system modeling using the Unified Modeling Language (UML). The results of the research are a web-based badminton sports hall management system, which can help badminton sports hall managers in building management and ordering schedules which can be done online.